The influence of attractiveness and expertise of influencers towards purchase intention mediated by brand image in the erigo clothing line brand in Indonesia - Suryakrisna, Adrian; Esti Susanti, Christina (Technium Social Sciences Journal, 2024)
The purpose of this study is to analyze the influence of attractiveness and expertise towards purchase intention mediated by brand image in the clothing line Erigo in Surabaya. This research is quantitative with a descriptive approach. The object of the study is the clothing line brand Erigo, and the criteria for the respondents are active social media users in Surabaya who are over 17 years old and who have seen the brand endorsement of Erigo. The sampling is done using non-probability sampling with the purposive sampling technique, and data is collected through direct questionnaire distribution. The analysis technique used in this research is Structural Equation Modeling-Linear Structural Relationships (SEM-LISREL) with the LISREL 8.80 application. The results showed that attractiveness and expertise have a positive and significant effect on brand image, and brand image has a positive and significant effect on purchase intention. In addition, the results also show that brand image is able to act as a mediating (intervening) variable for the influence of attractiveness and expertise on purchase intention. The suggestions for this research are to consider the direct relationship between the variables of attractiveness and expertise on purchase intention and to expand the respondent criteria.